2006
DOI: 10.7863/jum.2006.25.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Detection Rate of Early Fetal Echocardiography and In Utero Development of Congenital Heart Defects

Abstract: Early fetal echocardiography is feasible and allows the detection of most CHD. Congenital heart defects vary in appearance at different stages of pregnancy and may evolve in utero with advancing gestational age. Therefore, early fetal echocardiography should always be followed by echocardiography at mid gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 38 publications
4
67
0
6
Order By: Relevance
“…With a detection rate of ca. 50 %, atriventricular septal defects are the most frequently diagnosed heart defects in these series [32,33]. Isolated defects of the ventricular septum or the outflow tracts are much less commonly diagnosed correctly in the first trimester.…”
Section: Gefäße Hinter Dem Herzenmentioning
confidence: 99%
See 3 more Smart Citations
“…With a detection rate of ca. 50 %, atriventricular septal defects are the most frequently diagnosed heart defects in these series [32,33]. Isolated defects of the ventricular septum or the outflow tracts are much less commonly diagnosed correctly in the first trimester.…”
Section: Gefäße Hinter Dem Herzenmentioning
confidence: 99%
“…Published studies mainly concern data on high-risk collectives in which fetuses with increased nuchal translucency and/or aneuploidy are over represented. Here, detection rates of between 63 % and 70 % are given for complete echcardiographic examinations with consideration of the outflow tracts [33]. With a detection rate of ca.…”
Section: Gefäße Hinter Dem Herzenmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Very important criterion for the screening method is its simplicity, good sensitivity and specificity, acceptable reliability and low costs. 7,8 It was revealed that sensitivity of the fetal echocardiography could be improved by visualization of four-chamber view and depiction of great arteries outflow tracts in the same fetus. 9 Is the education of screeners alone sufficient to achieve that goal of the utmost importance for the improvement of fetal echocardiography as a screening method?…”
Section: Introductionmentioning
confidence: 99%